2007
DOI: 10.1176/ajp.2007.164.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Is Decreased Prefrontal Cortical Sensitivity to Monetary Reward Associated With Impaired Motivation and Self-Control in Cocaine Addiction?

Abstract: These findings suggest that in cocaine addiction 1) activation of the corticolimbic reward circuit to gradations of money is altered; 2) the lack of a correlation between objective and subjective measures of state motivation may be indicative of disrupted perception of motivational drive, which could contribute to impairments in self-control; and 3) the lateral prefrontal cortex modulates trait motivation and deficits in self-control, and a possible underlying mechanism may encompass a breakdown in prefrontal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
166
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 199 publications
(198 citation statements)
references
References 41 publications
29
166
3
Order By: Relevance
“…In drug dependency, the dorsal caudate is implicated in compulsive drug seeking and habit formation (Everitt et al, 2008;Koob and Volkow, 2010). Our finding is consistent with studies reporting decreased neural sensitivity in drug-dependent patients for nondrug-related rewarding stimuli (Buhler et al, 2010;Diekhof et al, 2008;Goldstein et al, 2007;Peters et al, 2011;Wrase et al, 2007) and with a hypothesis of nondrug rewards being undervalued in drug dependency (Hyman et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In drug dependency, the dorsal caudate is implicated in compulsive drug seeking and habit formation (Everitt et al, 2008;Koob and Volkow, 2010). Our finding is consistent with studies reporting decreased neural sensitivity in drug-dependent patients for nondrug-related rewarding stimuli (Buhler et al, 2010;Diekhof et al, 2008;Goldstein et al, 2007;Peters et al, 2011;Wrase et al, 2007) and with a hypothesis of nondrug rewards being undervalued in drug dependency (Hyman et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Fewer studies have investigated neural responses to nondrug-related rewards in dependent individuals. Decreased neural responses to nondrug-related rewards have been reported with cocaine (Garavan et al, 2000;Goldstein et al, 2007), alcohol (Wrase et al, 2007), nicotine, (Buhler et al, 2010;Peters et al, 2011) and opiate (Martin-Soelch et al, 2001) misuse. Investigation of neural responses to aversive stimuli in addiction is rare.…”
Section: Introductionmentioning
confidence: 98%
“…Providing validity to this underlying hypothesis, our current study is the first to document that, compared with healthy control subjects and even in the absence of behavioral differences between the groups, the ACC is hypoactive as measured with BOLD-fMRI during an emotionally salient task. These findings extend previous fMRI results where ACC hypoactivations were documented in CUD as compared with controls in response to emotionally neutral cognitive tasks (9), or where performance differed on similar cognitive (5-8) or other emotionally salient tasks (27). Our current results indicate that such ACC hypoactivations cannot be fully attributed to task difficulty.…”
Section: Discussionsupporting
confidence: 89%
“…However, we did not expect to find similar correlations between these measures of performance with the BOLD signal. Prior studies from our laboratory, using a different fMRI blocked-design task, showed lack of an association between these performance measures in the cocaine addicted but not control subjects; we attributed these results to impaired perception of inner motivation in drug addiction (Goldstein et al, 2007).…”
Section: Methodsmentioning
confidence: 65%